EFFECTS OF SLIP RATIO ON WEAR PERFORMANCE OF CLASS B WHEEL STEELS AGAINST SOFTER R260 RAIL STEELS USING THE TWIN DISC SETUP - Leso, Tshenolo Phinah; Siyasia, Charles; Mostert, Roelf; Moema, Joseph (The South African Journal of Industrial Engineering, 2022)
A train experiences different slip ratios at the wheel/rail contact point as it moves along the rail track, which influences the rolling contact fatigue (RCF) and wear properties of wheel and rail materials. This variation in slip ratios is caused by a change in contact area between the wheel and rail head at curves, as the slip ratio increases compared with when a train is moving on a straight track. When the train is moving on a straight track, the wheel is found to be in contact with the rail head; but that changes when moving around curves, as the wheel flange will now be in contact with the gauge corner of the rail, affecting the severity of wear. Therefore, more research needs to be done to understand the role that slip ratio plays in the wear performance of wheel and rail materials in order to be able to develop models or systems that could be used to predict preventive maintenance. The aim of this work was to investigate the effect of the slip ratio on the wear performance of class B wheels against softer R260 rail steels under rolling and sliding conditions, using a twin-disc setup developed at the University of Pretoria. The results showed that the severity of wear was heavily dependent on the slip ratio – i.e., it increased with the slip ratio, with class B wheels performing better than the softer R260 rail.